2009
DOI: 10.1063/1.3127602
|View full text |Cite
|
Sign up to set email alerts
|

The tissue diagnostic instrument

Abstract: Tissue mechanical properties reflect extracellular matrix composition and organization, and as such, their changes can be a signature of disease. Examples of such diseases include intervertebral disk degeneration, cancer, atherosclerosis, osteoarthritis, osteoporosis, and tooth decay. Here we introduce the tissue diagnostic instrument (TDI), a device designed to probe the mechanical properties of normal and diseased soft and hard tissues not only in the laboratory but also in patients. The TDI can distinguish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 25 publications
1
54
0
Order By: Relevance
“…In a concerted effort to develop a reliable method to directly quantify fracture risk in living patients in a noninvasive manner, we have developed a new diagnostic instrument, the Reference Point Indentation Instrument [4] (RPI) (aka. Tissue Diagnostic Instrument [5], Bone Diagnostic Instrument [6][7][8], and Osteoprobe [9]) that uses a controlled indentation protocol to investigate the micro-mechanical response of the tibia to a defined loading regime. Clinical trials by Diez-Perez have shown the RPI to be successful at discriminating between patients with and without fragility fracture [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a concerted effort to develop a reliable method to directly quantify fracture risk in living patients in a noninvasive manner, we have developed a new diagnostic instrument, the Reference Point Indentation Instrument [4] (RPI) (aka. Tissue Diagnostic Instrument [5], Bone Diagnostic Instrument [6][7][8], and Osteoprobe [9]) that uses a controlled indentation protocol to investigate the micro-mechanical response of the tibia to a defined loading regime. Clinical trials by Diez-Perez have shown the RPI to be successful at discriminating between patients with and without fragility fracture [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the distance measured with the strain gauge is the same as the distance that the probe further indents into the sample from the reference point. The elimination of the reference probe has the advantage of simplicity and of removing the possibility of soft tissue buildup and friction between the test probe and the reference probe as in other RPI Devices [7][8][9][10]. Further detail of the instrument operation has been reported previously by Bridges et al [19].…”
Section: Osteoprobementioning
confidence: 94%
“…V R , was correlated with the BioDent V R [7][8][9][10] and a standard Vickers hardness test. Cadaver samples of cortical bone were excised from the mid diaphysis of the tibia from two 83-year-old female donors.…”
Section: Measurement Correlations Bone Materials Strength Measured Wmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] We are interested in using long range AFM to study fractured bone, a sample with rough topography and deep features exceeding the actuation range of conventional AFM. Since the development of the Reference Point Indenter (RPI), [10][11][12][13][14][15] an instrument which directly quantifies bone fracture resistance by creating an indent in bone and measuring the depth of the indent produced, we have been eager to image these indents with long range AFM. Previously, we developed a long range AFM based on voice coil actuation with a range of the order of 1 mm in each axis.…”
Section: Introductionmentioning
confidence: 99%